Intrinsic Motivated Cervical Cancer Screening Intervention Framework - Hasan, MR; Gholamhosseini, H; Sarkar, NI; Safiuzzaman, SM (IEEE, 2018)
Cervical cancer turned into a reason of extreme mortality even though it is preventable. The expansion rate of cervical cancer is at alarming rate internationally, including both developed (e.g. New Zealand) and developing (e.g. Bangladesh) countries. This study considers survey data collected from Chittagong Medical College Hospital in Bangladesh and other secondary data from open sources. Studies have uncovered that younger women aged from 25 to 34 tend not to react to cervical screening program. Without regular cervical cancer screening, the early changes that could progress to cervical cancer suffering would not be picked up. This study aims to address these concerns by proposing a cervical screening intervention program to encourage women of all age group to participate in the screening program. The intervention could contribute to the health sector by decreasing the cervical cancer mortality rate and associated cost. The preliminary investigation shows that about 96% screening take-up following such intervention program suggesting that a proper intrinsic motivated cervical cancer intervention program is required.
Keywords: Cervical cancer; Intervention, mortality, morbity; Pap smear; Screening